2019
DOI: 10.1017/s0022215119000677
|View full text |Cite
|
Sign up to set email alerts
|

Value of patient-reported symptoms in the follow up of patients potentially cured of laryngeal carcinoma

Abstract: ObjectiveTo evaluate the significance of patients’ ability to recognise symptoms that signify recurrence.MethodsA retrospective analysis was conducted in Norway of demographic, clinical and follow-up data for patients with laryngeal carcinoma considered free of disease following treatment. The study included clinical data from 732 patients with glottic tumours and 249 patients with supraglottic tumours who were considered cured of disease. Data on the site, time and type of recurrence (symptomatic or asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In their study, 122 of 156 (78%) LSCC recurrences and second primary tumors were found within 3 year follow-up, and 94 of 156 (60%) recurrences and second primary tumors were detected on a routine follow-up visit [ 11 ]. In another study, 81% (103 of 127) of patients with stage I to IV glottic LSCC who developed a recurrence were symptomatic [ 12 ]. In our study of T1 patients, the number of symptomatic patients was substantially lower.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 122 of 156 (78%) LSCC recurrences and second primary tumors were found within 3 year follow-up, and 94 of 156 (60%) recurrences and second primary tumors were detected on a routine follow-up visit [ 11 ]. In another study, 81% (103 of 127) of patients with stage I to IV glottic LSCC who developed a recurrence were symptomatic [ 12 ]. In our study of T1 patients, the number of symptomatic patients was substantially lower.…”
Section: Discussionmentioning
confidence: 99%
“…In our ePROs program, we opted to administer multiple longitudinal surveys anchored with a clinical visit. Multiple surveys allowed for the analysis of the trajectory of treatment‐related side effects 4 and monitoring for recurrence 8‐10 . Incorporating survey delivery into a visit also improved adoption in the follow‐up setting (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that most recurrences of head and neck malignant neoplasms are detected through symptoms reported by patients, instead of physical examination of asymptomatic patients during follow-up 12 . Boysen et al 12:1-7 found "[…] a higher rate of symptomatic versus asymptomatic recurrences in glottic and supraglottic recurrences, particularly in the first two years of follow-up".…”
Section: Discussionmentioning
confidence: 99%